2003
DOI: 10.1196/annals.1290.038
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy and Cardioprotection

Abstract: Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in women after the age of 50 years in most developed countries. Estrogen deficiency plays a key role in causing CVD in women. Apart from the direct effect of ovarian hormones on the vessel wall, cessation of ovarian function and the consequent reduction of sex steroid hormone levels have important metabolic and pathological implications that negatively influence the cardiovascular system. Therefore, the increased incidence of CVD obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Recent studies confirm that the time elapsed after menopause is a relevant factor when taking the decision to recommend hormone replacement therapy (33,37,50). Indeed, a very recent study, showed that ''After 10 years of randomised…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies confirm that the time elapsed after menopause is a relevant factor when taking the decision to recommend hormone replacement therapy (33,37,50). Indeed, a very recent study, showed that ''After 10 years of randomised…”
Section: Discussionmentioning
confidence: 99%
“…15 Rosano et al (2003) suggested that hormone therapy had beneficial cardiovascular effects in early postmenopausal women, while it may have had detrimental effects on coagulative balance and vascular inflammation. 16 The administration route of HT appears to affect the fibrinolytic activity and the coagulation markers. Also, the oral route is associated with changes in the levels of coagulation and fibrinolysis markers, especially during the early period of use.…”
Section: Introductionmentioning
confidence: 99%
“…Key Words: 17␤-estradiol Ⅲ blood pressure Ⅲ estrogen receptor Ⅲ nitric oxide synthase Ⅲ autonomic nervous system T he increased incidence of cardiovascular disease in postmenopausal women has been attributed to the loss of estrogen (E2), 1,2 and it was observed that hormone replacement therapy confers cardiovascular benefits in these women. [1][2][3] In 1993, the Women's Health Initiative trial began recruiting Ͼ16 000 postmenopausal women to assess the benefits and risks of hormone replacement therapy on the incidence of heart disease, cancers, and fractures. 4 Surprisingly, the trial was terminated in 2002 because of increased risks of breast cancer and stroke.…”
mentioning
confidence: 99%
“…[1][2][3] In 1993, the Women's Health Initiative trial began recruiting Ͼ16 000 postmenopausal women to assess the benefits and risks of hormone replacement therapy on the incidence of heart disease, cancers, and fractures. 4 Surprisingly, the trial was terminated in 2002 because of increased risks of breast cancer and stroke.…”
mentioning
confidence: 99%